Gallery of best résumés - Noble, David F. (David Franklin), 1935- (JIST Works, 2004)
This textbook discusses the most important theories of internationalization, including Product Life-Cycle, Internalization, Location, International New Venture concepts, and others. These models are grounded to a considerable extent in the Transaction Cost Theory and the Resource-Based View as explained in the book. Relevant market entry strategies are explained in light of crucial determinants of international business decision making.